Diet-derived circulating antioxidants and risk of epilepsy: a Mendelian randomization study - Huang, Shicun; Chen, Yingqi; Wang, Yiqing; Pan, Shengjie; Lu, Yeting; Gao, Wei; Hu, Xiaowei; Fang, Qi (Frontiers in Neurology, 2024)
Previous studies suggest a link between diet-derived circulating antioxidants and epilepsy, but the causal relationship is unclear. This study aims to investigate the causal effect of these antioxidants on epilepsy.To assess the causal link between dietary antioxidants and epilepsy risk, we conducted a two-sample Mendelian randomization (MR) analysis. This involved examining antioxidants such as zinc, selenium, α-and γ-tocopherol, vitamin A (retinol), vitamin C (ascorbate), and vitamin E (α-tocopherol). We utilized instrumental variables (IVs) which were genetic variations highly associated with these commonly used antioxidants. Exposure data were sourced from a comprehensive genome-wide association study (GWAS). We aggregated data from the International League Against Epilepsy (ILAE) Consortium sample, which included various types of epilepsy, as an outcome variable. Finally, we applied the inverse variance weighting method and conducted sensitivity analyses for further validation.Based on the primary MR estimates and subsequent sensitivity analyses, the inverse variance weighting (IVW) method revealed that a genetically predicted increase in zinc per standard deviation was positively associated with three types of epilepsy. This includes all types of epilepsy (OR = 1.06, 95% CI: 1.02-1.11, P= 0.008), generalized epilepsy (OR = 1.13, 95% CI: 1.01-1.25, P= 0.030), and focal epilepsy (documented hippocampal sclerosis) (OR = 1.01, 95% CI: 1.00-1.02, P= 0.025).However, there is no evidence indicating that other antioxidants obtained from the diet affect the increase of epilepsy either positively or negatively.Our research indicates that the risk of developing epilepsy may be directly linked to the genetic prediction of zinc, whereas no such association was found for other antioxidants.